The role of animals in buffering against cisgenderism in and beyond family contexts for trans young people living in Australia - Riggs, Damien W. (Journal of family violence, 2024)
Purpose: The purpose of the study reported in this paper was to explore the role of animals in buffering against cisgenderist violence experienced by trans young people. Method: Interviews were conducted with 17 Australian trans young people and one of their parents who spoke with us about their relationships with their animals living in the home, including in terms of animals providing a protective function against the negative effects of cisgenderism. The transcribed interviews were analyzed thematically. Results: Thematic analysis resulted in the development of three themes. First, at the psychological level, animals helped young people to combat feelings of dysphoria, wrought by the violent effects of social norms about gender. Second, at the interpersonal level, animals helped to soothe young people when they were faced with less than supportive or indeed hostile responses from family members and other people in their lives. Third, at the community level, the companionship provided by animals offered a buffer against feelings of marginalization premised on cisgenderist social norms. Conclusions: All three themes speak to the importance of conceptualizing violence in family contexts as more than just the obvious: as encompassing more subtle forms of marginalization that in their net effect may constitute forms of violence or microaggressions. As a counter to these subtle forms of violence, animals are thus perceived as playing an important role as confidantes, as offering a place of non-judgemental safety, and as a touchstone to the more-than-human.